Integration of Digital Technologies for Engineering Innovation (Ciencias de la Ingeniería y Aplicadas, 2025)
Technological and digital evolution is revolutionizing modern education by facilitating new opportunities to enhance learning processes. Many of these advances have had a measurable impact on educational environments, as evidenced by the increasing use of digital platforms, technological tools, and virtual learning environments. These elements support the development of new methodologies that foster active learning. Recent studies indicate that over 80% of educational institutions have incorporated technology into their teaching processes, improving academic performance and promoting skills such as critical thinking and digital literacy. However, challenges remain in terms of equitable access, as 30% of students lack adequate connectivity or devices. Therefore, the need for public policies that promote digital equity is emphasized.
Keywords: technology; digital technologies; virtual reality; artificial intelligence